Vodcast as ideating medium in STEM lesson plan in teaching heat transfer - Guden, Jester Mark; Alguno, Arnold C.; Sayson, Noel Lito B.; Magsayo, Joy R.; Jr., Sotero O. Malayao (International Journal of Evaluation and Research in Education (IJERE), 2024)
This study attempts to link the clay soil in the locality to the topic of heat transfer as a contextualization point. It attempted to slightly modify the seven-step STEM lesson by having the part of the prototyping be first tried by the teacher, thereby having a change-of-hat to anticipate the ‘what if’ questions of the students. The teacher-researchers experimentation provided critical information to scaffold the students in the prototyping part.  The evaluation of experts shows that the modified STEM lesson can be an excellent tool and the vodcast has been found to be a very satisfactory component of the STEM lesson. It is described as a very useful material in teaching heat transfer and related thermodynamics concepts and is highly recommended for use in both distance learning and face-to-face modality. Further, the clay oven exploration has come up with a refined clay oven production process, wherein the clay oven prototype has the capacity for the contextualization of heat transfer. It is recommended that a formal implementation be conducted to refine and standardize the lesson delivery.